KONTEN VISUAL STORYTELLING AKUN TIKTOK @KOLLAINFOREST DALAM PEMBENTUKAN BRAND IMAGE DI KALANGAN FOLLOWERS - R. Agni Najwa Madenda; Hudi Santoso (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The rapid development of social media, particularly TikTok, has transformed how audiences consume information and form perceptions of a brand, making visual storytelling content an essential element in digital marketing communication strategies. However, studies examining the influence of visual storytelling on brand image formation on TikTok are still limited. This study aims to analyze the effect of visual storytelling content on the formation of brand image on the @kollainforest TikTok account among its followers. This research employs a quantitative approach using a survey method involving 100 respondents who are followers of the @kollainforest account. Data were collected through questionnaires using a Likert scale and analyzed using classical assumption tests and simple linear regression. The results show that visual storytelling content is categorized as high across all dimensions, while brand image is also categorized as high. The regression analysis indicates a positive and significant effect of visual storytelling on brand image, with a regression coefficient of 0.401 and a significance value of < 0.001. Furthermore, the coefficient of determination (R Square) is 0.438, indicating that visual storytelling contributes 43.8% to the formation of brand image, which is considered a moderately strong effect. These findings suggest that improving the quality of visual storytelling content can strengthen brand image in the minds of the audience. Therefore, businesses and content creators are encouraged to optimize creative, consistent, and communicative visual content as a strategy to build a positive brand image.